A Global Inventory of Ice‐Related Morphological Features on Dwarf Planet Ceres: Implications for the Evolution and Current State of the Cryosphere. Issue 7 (2nd July 2019) - Sizemore, H. G.; Schmidt, B. E.; Buczkowski, D. A.; Sori, M. M.; Castillo‐Rogez, J. C.; Berman, D. C.; Ahrens, C.; Chilton, H. T.; Hughson, K. H. G.; Duarte, K.; Otto, K. A.; Bland, M. T.; et al.
Abstract: We present a comprehensive global catalog of the geomorphological features with clear or potential relevance to subsurface ice identified during the Dawn spacecraft's primary and first extended missions at Ceres. We define eight broad feature classes and describe analyses supporting their genetic links to subsurface ice. These classes include relaxed craters ; central pit craters ; large domes ; small mounds ; lobate landslides and ejecta ; pitted materials ; depressions and scarps ; and fractures, grooves, and channels . Features in all classes are widely distributed on the dwarf planet, consistent with multiple lines of observational evidence that ice is a key component of Ceres' crust. Independent analyses of multiple feature types suggest rheological and compositional layering may be common in the upper 10 km of the crust. Clustering of features indicates that ice concentration is heterogeneous on nearly all length scales, from 1 km to hundreds of kilometers. Impacts are likely the key driver of heterogeneity, causing progressive devolatilization of the low latitude and midlatitude crust on billion‐year timescales but also producing localized enhancements in near surface ice content via excavation of deep ice‐rich material and possible facilitation of cryomagmatic and cryovolcanic activity. Impacts and landslides may be the dominant mechanism for ice loss on modern Ceres. Our analysis suggests specific locations where future high‐resolution imaging can be used to probe (1) current volatile loss rates and (2) the history of putative cryomagmatic and cryovolcanic features. The Cerean cryosphere and its unique morphology promise to be a rich subject of ongoing research for years to come. Plain language summary: Planetary scientists are interested in understanding where ice is located in the solar system for two reasons. First, water is necessary to sustain life as we know it, so extraterrestrial ice may provide habitats for past or present life. Second, water ice can be used to produce rocket fuel; in the future, ice may be mined from asteroids, moons, and planets to fuel spacecraft carrying humans. Ceres has been predicted to contain large amounts of ice for decades. When the Dawn spacecraft arrived at Ceres, a major goal for the science team was confirming the presence of ice and understanding how it is distributed beneath the surface. One aspect of that investigation was identifying landforms (features like mountains or craters on the surface) whose appearance indicates the presence of ice. In this study, we compiled a catalog and global maps of all of the "icy" landforms identified during Dawn's primary mission at Ceres. We used these maps, together with detailed analysis of each type of landform, to develop a global picture of how ice is distributed in Ceres' crust. We found that the concentration of ice was spatially variable and that layering of icy and less icy materials may be common. We also identified specific areas of Ceres that may be particularly ice‐rich, so that future missions can target these areas for more analysis. Key Points: We present a global catalog and maps of the morphological features relevant to subsurface ice identified during the Dawn mission at Ceres Morphology suggests ice concentration is heterogeneous in the upper kilometers of Ceres' crust; impacts likely contribute to heterogeneity We highlight locations where future analysis may provide insights into putative cryovolcanic features and current H2 O loss mechanisms